Strategies of self-regulation of learning (SRL) as a predictor of academic achievement for students of first year secondary: Correlational research - TAIBA, Abdeslam; BELAID, Ahmed (Journal of Human Sciences, 2020)
This study aims to know the relationship between self-regulation strategies for learning, academic achievement and predictability of academic achievement, Predicting academic achievement through applying these strategies. The study was applied to a sample of (244) secondary school pupils, Al-Sadiq Talbi, in the city of (Laghouat).The researchers followed the steps of the descriptive approach, and processed the results using the (SPSS) software, (19) version to calculate correlation coefficients, multiple linear regressions and test differences (T) to ensure the validity of hypotheses.The results engender to a positive correlation between self-regulation strategies and academic achievement. There are also gender differences in self-regulation learning strategies for females. Academic achievement can be predicted through some strategies: (planning and goal setting, listening and remembering, helping others, cognitive maps).